Root Canal Obturation by Electrochemical Precipitation of Calcium Phosphates - Koch, Maximilian; Palarie, Victor; Göltz, Maximilian; Kurzer, Marvin; Zulla, Manuel; Rosiwal, Stefan; Willner, Marian; Burkovski, Andreas; Karl, Matthias (Applied Sciences, 2022)
Achieving adequate disinfection and preventing reinfection is the major goal in endodontic treatment. Variation in canal morphology and open porosity of dentine prevents achieving complete disinfection. Questionable biocompatibility of materials as well as a lack of sealing ability questions the usefulness of current obturation methods. With a novel disinfection approach based on the use of boron-doped diamond (BDD) electrodes having shown promising results it was the goal of this series of experiments to investigate the possibility of BDD-mediated in situ forming of a biocompatible obturation material. A combination of calcium phosphate and maleic acid was used as precursor solution while Ion Chromatography Mass Spectrometry (IC-MS), Raman spectroscopy (RAMAN), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), dye penetration and micro-computed tomography (µCT) were applied for characterizing the precipitate. It was possible to achieve a BDD-mediated precipitation of brushite in a clinically applicable timeframe. However, tight sealing of the canal system based on brushite could not be achieved.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Boron-doped diamond; Brushite; Hydroxyapatite; Obturation; Reactive oxygen species